Bimbingan Kelompok Meningkatkan Keterampilan Berkomunikasi Siswa - Erwin Erlangga (Fakultas Psikologi, Universitas Islam Negeri (UIN) Sunan Gunung Djati Bandung, 2017)
This study aims to improve communication skills of the seventh-year students in MTs. Annur Karangjunti Kabupaten Brebes Jawa Tengah. Their low communication skills shown by unpolite interaction with the teacher, hurt others’ feelings, and passive in the class. The sample were 35 students from 177 of population. This study used group guidance service and communication skills scale. The data analysis technique used t-test. According to the test results, there was an increase in the communication skills of the students, group 1 was 25,66%, group 2 was 21,5%, and group 3 was 28,54%. In conclusion, group guidance service can influence communication skills of the seventh-year students in MTs Annur Karangjunti Kabupaten Brebes Jawa Tengah.